Horizons of modern molecular dynamics simulation in digitalized solid freeform fabrication with advanced materials. (December 2020) - Goel, S.; Knaggs, M.; Goel, G.; Zhou, X.W.; Upadhyaya, H.M.; Thakur, V.K.; Kumar, V.; Bizarri, G.; Tiwari, A.; Murphy, A.; Stukowski, A.; Matthews, A.
Abstract: Our ability to shape and finish a component by combined methods of fabrication including (but not limited to) subtractive, additive, and/or no theoretical mass-loss/addition during the fabrication is now popularly known as solid freeform fabrication (SFF). Fabrication of a telescope mirror is a typical example where grinding and polishing processes are first applied to shape the mirror, and thereafter, an optical coating is usually applied to enhance its optical performance. The area of nanomanufacturing cannot grow without a deep knowledge of the fundamentals of materials and consequently, the use of computer simulations is now becoming ubiquitous. This article is intended to highlight the most recent advances in the computation benefit specific to the area of precision SFF as these systems are traversing through the journey of digitalization and Industry-4.0. Specifically, this article demonstrates that the application of the latest materials modelling approaches, based on techniques such as molecular dynamics, are enabling breakthroughs in applied precision manufacturing techniques. Highlights: The article provides insights of using atomic simulations as a digital manufacturing tool. There is an acute need for inserting new materials into current and future manufacturing. Recent advances in solid free form fabrication, particularly, R2R technology was highlighted. The developments in high-performance molecular dynamics were highlighted. Transferability of a force field can be checked by performing vapor growth simulations.